Clinicopathological features of pulmonary mucinous adenocarcinoma: A descriptive analysis. (2022) - Bradbury, Michelle; Akurang, Deborah; Nasser, Abdullah; Moore, Sara; Sekhon, Harmanjatinder S; Wheatley-Price, Paul
Abstract: Background: : Mucinous adenocarcinoma is a rare subtype of lung cancer characterized by abnormal mucin production. We sought to investigate the clinical and pathological features of pulmonary mucinous adenocarcinomas and to identify prognostic factors. Methods: : This was a single-institution retrospective review of patients with pulmonary mucinous adenocarcinoma diagnosed between January 1, 2015 and December 31, 2020. Descriptive analysis included demographics, diagnostic data, and treatment modalities. The primary outcome was overall survival (OS). Results: : Fifty-six patients were included in the study. Median age was 65 years (range: 26-84), 30 (54%) were female, 48 (86%) had a smoking history, and 41 (73%) patients had ECOG performance status 0-1. Nearly half (26, 46%) were stage IV at presentation, while 11 (20%) presented as stage I, 10 (18%) stage II, and 9 (16%) stage III. Biomarker testing increased through the study period. Where performed, 4/48 (8%) cases were ALK positive, but there were no EGFR cases identified (0/36). Only 3/20 cases had PD-L1 expression >50%. Curative intent therapy was performed in 23 patients (17 had surgery +/- chemotherapy/radiation, 4 had radiotherapy alone, 2 had chemoradiation). Median OS in the entire population was 16.1 months (m). OS by stage was 50.0m for stage I, not reached for stage II, 20.7m for stage III, and 8.1m for stage IV. Conclusions: : The overall prognosis of pulmonary mucinous adenocarcinoma appears similar to that of non-mucinous adenocarcinomas, with distinct differences noted in the incidence of oncogenic driver mutations, particularly an absence of EGFR mutations.